Data Communication in Internet of Things: Vision, Challenges and Future Direction - Jammel Mona (Universitas Ahmad Dahlan, 2018)
Ubiquitous technologies based heterogeneous networks has opened a new paradigm of technologies, which are enabled with various different objects called Internet of things (IoT). This field opens new door for innovative and advance patterns with considerable potential advantages in the shape of plethora of monitoring and infotainment applications around us. Data communication is one of the significant area of research in IoT due to its diverse network topologies, where diverse gadgets and devices have integrated and connected with each other. In order to communicate among devices and users, routing should be relible, secure and efficient. Due to diverse and hetrogenous netwok environment, the most of the existing routing solutions do not provide all quality of services requirement in the network. In this paper, we discuss the existing routing trend in IoT, vision and current challenges. This paper also elaborates the technologies and domains to drive this field for future perspectives. The paper concludes with discussion and main points for new researchers in terms of routing to understand about current situation in IoT.